Let g(s) = s3 + 11*s2 + 10*s. Let a be g(-10). Suppose a = 6*f - 3*f. Solve -y = -f*y + 5 for y.
-5
Let n = -2 - -5. Suppose -4 = -d + n. Solve -27 = 5*k - d for k.
-4
Let j(t) = 9*t + 3. Let z(w) = -10*w - 3. Let k(x) = 4*j(x) + 3*z(x). Let g be k(3). Suppose 3*v = -m + g - 10, m = v - 5. Solve 0 = 3*a + 10 - v for a.
-2
Suppose 3*s + 2*s - 10 = 0. Suppose 0*j = -s*j + 8. Solve q = -3*q + j for q.
1
Suppose 3*k + 2*j = 9, -5*k = -j + 2*j - 8. Solve c - 3 = -k for c.
2
Let c be 25-1(-2)/5. Let t be (((-12)/(-7))/(-2))/((-318)/1484). Solve 2*k = t*k + c for k.
-5
Let j = 1 + 1. Solve -3*p = -j - 4 for p.
2
Suppose 1 = -4*t + 9. Solve 2*c = -t*c + 4 for c.
1
Let m© be the third derivative of -c5⁄60 + c4⁄6 + 5*c3⁄6 - 2*c2. Let h be m(4). Solve h*i - 3 = 6*i for i.
-3
Let w(v) = -6*v3 - v2 + v + 1. Let q be w(-1). Let u be (-40)/(-12)*3⁄2. Suppose -u*j + j = -h + 55, 0 = -2*h + j + 75. Solve -q*x - 10 = -h for x.
5